Naive Yearling Steers Consume Little Sericea Lespedeza in the Kansas Flint Hills - C. A. Sowers; J. D. Wolf; W. H. Fick; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective of this study was to characterize diets selected by steers grazing sericea lespedeza (Lespedeza cuneata)-infested native tallgrass pastures. Study Description:The experiment was conducted on eight native tallgrass pastures located in Woodson County, KS, at the Kansas State University Bessner Range Research Unit during the 2015 and 2016 growing season. Pastures were burned annually in April and stocked with yearling steers (n = 281/year; initial body weight = 582 ± 75 lb) at a relatively high stocking rate (2.7 acres/steer) from April 15 to July 15. Basal frequency of sericea lespedeza was 2.9 ± 2.43% during the period of our experiment. Four 328-ft transects were laid out in a north-south gradient in each pasture. Following a 2-week adaptation period, fecal samples were collected bi-weekly from fresh fecal pats along each transect from May 1 to July 15, annually. Fecal samples were prepared and viewed under a compound microscope to identify and count plant fragment species. These data were used to determine the frequency of which plant species appeared in steer diets. The Bottom Line:In this experiment, grasses comprised not less than 88.4% of steer diets, whereas forbs comprised not more than 11.6% of steer diets. Sericea lespedeza comprised only a minor proportion of grazing steer diets. This finding highlights the difficulty in achieving control over sericea lespedeza using grazing by yearling cattle alone.
Keywords: botanical composition; sericea lespedeza; yearlings